Ischemic stroke as a manifestation of atrial myxoma. A case presentation - María Gabriela Balarezo García; Diego Armando Suárez; Olivia Elizabeth Altamirano Guerrero (Medisur)
Cerebrovascular disease is one of the main causes of death worldwide. Multiple factors trigger ischemic strokes, including cardiac tumors such as atrial myxoma. A 32-years-old female patient,  who on physical examination showed motor aphasia, right fascio-brachio-crural hemiplegia and discrete vertical gaze paresis with nystagmus is presented. Imaging studies were performed (skull tomography, transthoracic echocardiogram and angiotomography of neck vessels) suggestive of systemic embolization in the left carotid territory, secondary to the fragmentation of a cardiac tumor. It was decided to refer the patient to cardiovascular surgery for carotid endarectomy with excision of the cardiac tumor, which progressed satisfactorily. Neurological damage persisted due to the time elapsed between diagnosis and treatment. Taking into account the low frequency of cardiac myxoma and the possibility of being associated with ischemic stroke, it was decided to present this case.